In situ microfluidic fabrication of SERS nanostructures for highly sensitive fingerprint microfluidic-SERS sensing. Issue 19 (28th January 2015) - Parisi, Joseph; Dong, Qiuchen; Lei, Yu
Abstract : A microfluidic-SERS device has been fabricated via a facile in situ galvanic replacement for ultrasensitive detection of pesticides and herbicides. Abstract : A microfluidic device with integrated silver nanoparticles (AgNPs) was fabricated via in situ galvanic replacement of a pre-patterned copper substrate in a microfluidic channel. The integrated microfluidic device with AgNPs serves as a highly active Raman substrate which can be applied for in-channel surface-enhanced Raman scattering (SERS). Preparation of the SERS active substrate and subsequent SERS experiments are all completed within the microfluidic device allowing for easy integration and application. In conjunction with the high sensitivity, easy fabrication and mobility of the microfluidic device, the developed microfluidic-SERS system provides an excellent sensing platform for sensitive, real-time fingerprint detection of target molecules. Crystal violet is first used as a model compound to demonstrate the effectiveness of the microfluidic-SERS system. Specifically, the in situ fabricated SERS active substrate demonstrates high sensitivity and exhibits an apparent enhancement factor of 2.2 × 10 7, high robustness and reusability, making it a perfect fit for the real time detection of pesticides. Finally the detection of pesticides and herbicides such as Carbofuran and Alachlor as low as 5 ppb was demonstrated using the as-developed microfluidic-SERS system. This study opens a new avenue to fabricate an integrated microfluidic-SERS sensing system with high performance.